Controllable wavelength conversion based on soliton dynamics in mid-infrared fiber - Shen, Kangle; Yang, Jian; Zhao, Jiayi; Yang, Xinyu; Yang, Hua (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
We provide a convenient way to actively control the wavelength conversion of probe waves based on the soliton dynamics in the As2S3 fibers. In this paper, it is found by numerical calculation that wavelength conversion occurs in the frequency domain due to the existence of refractive index barrier. By adjusting the collision position of pump pulse and probe pulse to realize the conversion of probe pulse wavelength, the effect of the power and the incident wavelength of the probe wave on the wavelength conversion are also discussed. This frequency domain conversion is of great use in the mid-infrared region, for example, all-optical conversion switches.
Optica Applicata, Vol. 53, 2023, nr 3, s. 419-429
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; soliton dynamics; photonic crystal fiber; all-optical conversion switches